2016
DOI: 10.1002/ldr.2633
|View full text |Cite
|
Sign up to set email alerts
|

The Resilience of Ethiopian Church Forests: Interpreting Aerial Photographs, 1938–2015

Abstract: Church forests collectively represent the only surviving remnants of the original montane forest, serving as critical sanctuaries for many of Ethiopia's endangered and endemic plant and invertebrate taxa. Modern inventories of church forests suggest that they are vulnerable to degradation because of their small size and isolation. The aim of this study is to use historical air photos from the period of the Italian occupation of Ethiopia (1935–1941) to measure changes to church forests over a ~80‐year time span… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 40 publications
(81 reference statements)
4
30
0
Order By: Relevance
“…(b)–(e) Normalized Difference Vegetation Index (NDVI) from 1984–2014 based on 30 × 30 m USGS Landsat satellite data; vegetation density was calculated for each church forest and the surrounding matrix (mean NDVI of a 500 m buffer surrounding each forest). The maps show relative stability of the forest fragment size over the past 30 years (consistent with findings by Scull et al ). Maps do reveal some vegetation loss since 1984 along the northeastern edge of the forest, as well as expansion of the clearing at the center of the forest since 1994.…”
Section: Methodssupporting
confidence: 89%
“…(b)–(e) Normalized Difference Vegetation Index (NDVI) from 1984–2014 based on 30 × 30 m USGS Landsat satellite data; vegetation density was calculated for each church forest and the surrounding matrix (mean NDVI of a 500 m buffer surrounding each forest). The maps show relative stability of the forest fragment size over the past 30 years (consistent with findings by Scull et al ). Maps do reveal some vegetation loss since 1984 along the northeastern edge of the forest, as well as expansion of the clearing at the center of the forest since 1994.…”
Section: Methodssupporting
confidence: 89%
“…These changes have significantly affected almost all terrestrial biomes (Baumgartner and Cherlet 2016;Borrelli et al 2017;Zhou et al 2017). To underpin this, Baumgartner and Cherlet (2016), Scull et al (2017), Temesgen and Wei (2018) confirmed that these impacts are pronounced in Sub-Saharan Africa. Besides, numerous anthropogenic disturbances have amplified the problem by affecting the ecosystem functions and services (Cork and Shelton 2000;FAO 2011;.…”
Section: Introductionmentioning
confidence: 93%
“…Significant gains in areas are observed on farmland and shrub land, as well as water body implies that the major driver of land LCLU change along the coastal zone is crop-agriculture. Obviously, crop farming that has increased in 16 years is threatening the health status of the coastal zone, like many other Sub-Saharan African ecosystems, as supported by Scull et al (2017) and . The net increase in farmland indicates a substantial expansion of cultivated land for crop production.…”
Section: Farmland Expansionmentioning
confidence: 99%
“…The potential of the APs of Ethiopia has been so far utilized in studies on forest and land cover change (e.g., Reid et al, 2000;Salvini, Riccucci, & Francioni, 2012;Zeleke & Hurni, 2001). The recently recovered APs of Ethiopia from the 1930s start being used in land-cover and forest-cover change studies (Asfaha, 2015;Scull et al, 2017). Gully erosion, a burning problem in Ethiopia, was addressed using APs in several studies (e.g., Daba, Rieger, & Strauss, 2003;Frankl, Poesen, Haile, Deckers, & Nyssen, 2013;Kropáček et al, 2017).…”
Section: Aerial Photography In Ethiopiamentioning
confidence: 99%